Maternal attachment representation in relation to emotional availability and discipline behavior - Negrão, Mariana (2017)
Maternal attachment representations have been investigated in relation to sensitivity and emotional support, but rarely in relation to other important areas of daily parent–child interactions in early childhood, like limit setting and discipline strategies. This study investigates maternal attachment representations in relation to parenting sensitive and discipline behaviours. The sample consists of 37 Portuguese high-risk severely economically disadvantaged mothers and their 1- to 4-year-old children, that responded to the Adult Attachment Interview, and were observed in play and discipline interaction contexts. The results showed that a more preoccupied state of mind was related to less emotional availability in free play interaction with child. A more secure attachment representation was related to more psychologically controlling discipline tactics. These findings highlight the relevance of maternal attachment states of mind in understanding parenting practices in several domains, and are discussed in light of sociocultural factors